Adolescents Demonstrate Greater Gait Balance Control Deficits After Concussion Than Young Adults. (March 2015) - Howell, David R.; Osternig, Louis R.; Chou, Li-Shan
Background: Age has been described as a factor that affects recovery after concussion. The recommended management protocol is to treat adolescents in a more cautious manner than adults. However, few studies have prospectively and longitudinally assessed the way these age groups perform on motor tasks after concussion. Purpose: To examine dual-task gait balance control deficits after concussion in a group of adolescents and young adults in reference to matched control subjects within 72 hours of injury and throughout 2 months after injury. Study Design: Cohort study; Level of evidence, 2. Methods: Adolescents and young adults who sustained a concussion and individually matched controls completed a whole-body motion gait analysis while simultaneously performing a cognitive task. Subjects with concussion reported to the laboratory within 72 hours after injury and at the following time points: 1 week, 2 weeks, 1 month, and 2 months after injury. Control subjects completed the same protocol at similar time points. Gait balance control measurements included whole-body center-of-mass (COM) medial-lateral displacement/velocity and anterior velocity. Results: A total of 38 subjects with concussion, 19 young adults (mean± SD age, 20.3 ± 2.4 years) and 19 adolescents (mean± SD age, 15.1 ± 1.1 years), and 38 individually matched control subjects were tested. Within 72 hours of injury, adolescents displayed significantly greater COM medial-lateral displacement ( P = .001) and peak velocity ( P = .001) relative to their control group, and the young adult concussion group displayed significantly less peak COM anterior velocity than their control group ( P = .01). Across the 2 months of testing, adolescents with concussion displayed significantly greater total COM medial-lateral displacement than did adolescent controls ( P = .001), while young adults with concussion did not significantly differ from their matched controls ( P = .07). Conclusion: An examination of gait balance control during dual-task walking revealed that after concussion, in reference to matched controls, adolescents demonstrated greater gait balance control deficits than did young adults initially and throughout the 2-month postinjury period, supporting the recommendation of conservative management for adolescents after concussion.